Hubungan Literasi Gizi dan Pengetahuan Gizi terhadap Kejadian Stunting: A Scoping Review: Hubungan Literasi Gizi dan Pengetahuan Gizi terhadap Kejadian Stunting: A Scoping Review - Wahyuni, Fani Cahya; Karomah, Ulfatul; Basrowi, Ray Wagiu; Sitorus, Nova Lidia; Lestari, Lily Arsanti (Universitas Airlangga, 2023)
Background: Globally, the incidence of stunting in children under five has declined over the past few decades. However, there are regional and in-country disparities. In Indonesia, the prevalence of stunting increased from 25.7% to 30.8% between 2013 and 2018. This upward trend is associated with negative consequences such as reduced academic potential, increased risk of noncommunicable diseases, increased healthcare costs, and reduced productivity. Maternal nutrition literacy is a contributing factor to stunting. Therefore, strengthening maternal nutrition literacy can help reduce stunting. Objectives: This study aims to examine the relationship between maternal nutrition literacy and maternal nutrition knowledge with the incidence of stunting in children under five. Methods: The literature search was conducted using databases, namely PubMed, Scopus, and ScienceDirect, and followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and Population, Intervention, Comparison, Outcome, and Study Design (PICOS) frameworks. Discussion: Only 13 out of 630 articles were eligible. Among them, four articles showed a significant correlation between nutrition knowledge and literacy with the incidence of stunting in lower-middle-income countries. In upper-middle-income countries, seven articles showed a significant correlation between nutrition literacy and knowledge with the incidence of stunting. Conclusions: There is a significant relationship between nutrition literacy and nutritional knowledge with the incidence of stunting. Nutrition literacy and knowledge can be related to infant and young child feeding, selection and preparation of nutritional and healthy foods, child growth and development, stunting prevention, access to health services, food security, and traditional food nutrition knowledge.